SYNERGY OF HALAL LITERACY AND SELF DECLARE HELPING MSMEsACHIEVE THE HALAL MANDATORY FOR HALAL TOGETHER - Atieqoh, Siti; Yumasdaleni, Yumasdaleni; Kustini, Kustini (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The Indonesian Mandatory Halal Policy has opened up opportunities and challenges for Micro, Small and Medium Entrepreneurs (MSMEs). This article emphasizes the importance of Halal food literacy and the use of the Self declareprogram to maximize this potential. The synergy between literacy and Self declareallows MSMEs to increase their competitiveness in domestic and international markets, as well as reach growing Muslim consumers. This article also discusses how Halal food literacy and the Self declareprogram can help MSMEs overcome challenges in facilitating the Halal Certification process in achieving Halal Mandatory, with a synergistic strategy to support this achievement. Synergistic Strategy are in the form of: 1) Training and education, the Government and related institutions can organize training and education about Halal food and the Self declareprogram for MSMEs). 2) Assistance, the Government and related institutions can provide assistance to MSMEs in the halal certification process. 3) Facilities and convenience, the Government and related institutions can provide facilities and convenience for MSMEs in participating in the self declare program. With a strong understanding of halal certification and effective use of the self declare program, MSMEs can understand the certification process, meet Mandatory Halal requirements, and save time and money. Through a qualitative approach, this research will look at the level of Halal food literacy among MSMEs, identify the contribution of the self declare program in strengthening Halal food literacy, and evaluate the effectiveness of the synergy between these two factors in achieving the Halal Mandatory. Data is collected through interviews and related documentation studies. It is hoped that the results of this research will provide a deeper understanding of the importance of halal food literacy and the implementation of the self declare program for MSMEs in meeting established halal standards, as well as provide useful recommendations for relevant stakeholders to improve quality and compliance with the Halal Mandatory in Indonesia.